Perilaku Berbisnis dan Implementasi Manajemen dalam Novel Harga Teman Design, Resign, Redesign Karya Debora Danisa - Avieka Hamada Kusumayudi; Dessyana Suryawandari; Eva Dwi Kurniawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Business is an activity that includes economics carried out individually or in groups with the aim of making a profit. In a business that is created, the entrepreneur will definitely try to create ideas that are new and unique in each business. The aim of this research is to describe business behavior and management implementation in the novel Harga Teman by Debora Danisa. This type of research uses a qualitative approach. The data collection technique used is listening and data text collection. The listening method is a way to obtain data by listening to the story facts and economic problems that occur in the novel. The materials used to collect data come from novels that have been read. The results of the research explain that the content of the story that occurred is truly relevant in the real world, where building a business requires the implementation of the basics of management and an unyielding behavior. Uncertain economic conditions subtly require entrepreneurs to be able to survive under any conditions. In business, it turns out that these factors are very necessary for smooth business continuity.